Traumatic Memories, Histories and Sexual Exploitation of Women in Akachi Adimora-Ezeigbo’s Trafficked and Abubakar Adam Ibrahim’s Season of Crimson Blossoms - Madumere, Laurel Chikwado (Journal of Gender and Power, 2022)
This study examines the traumatic effects of violence, human trafficking and sexual exploitation of young women. The intent is to discover the extent and complexity of the problems of human trafficking, sexploitation, violence and the resultant trauma; and how literature as imitation of life has captured the phenomena in form of fiction. Therefore attention is paid to Akachi Adimora-Ezigbo’s Trafficked (2008) and Abubakar Adam Ibrahim’s Season of Crimson Blossoms (2015) as canonical novels that have portrayed the issues from a unique Nigerian perspective. The paper is qualitative in approach and adopts Cathy Caruth’s and Kali Tal’s strand of trauma theory as its framework. The reason for the framework is to enable the researcher, on the one hand, to probe the emotional and psychological states of the characters and on the other hand, to relate the experiences of the characters to those of real human situations, in the societies that gave birth to the novels; to identify how fiction and reality come together, literarily, to hold conversations. In that case the paper pays very close attention to the subject matters that are associated with human trafficking and violence such as: sexploitation, slavery, trauma, healing, psycho-social problems, genocide, ethnic cleansing and others. The significance of this paper is its ability to identify the therapeutic essences of art, especially the literary art; the power of storytelling in healing emotional injuries. It discovers that trauma is a wound of the mind which requires greater attention than it receives in postcolonial Nigerian literature.